android kotlin tutorials - rosari j (APMBA (Asia Pacific Management and Business Application), 2014)
There was an article on apmba a while back about 7 reasons why we should start studying Kotlin for Android in 2018. The reasons why we should start learning Kotlin for Android in 2018 are now clear, yet learning materials for beginners to create Android apps using Kotlin are still scarce. As a result, the author will help readers who are looking for resources to learn how to construct Android apps using the Kotlin programming language.